European union wood biomass demand for energy purposes and its influence on U.S. southeastern forest market and carbon storage - Chudy, Rafal (SLU/Southern Swedish Forest Research Centre, 2011)
Energy supply combined with reduction of greenhouse gas emissions is a global concern. The European Union (EU) has set an ambitious target to achieve 20% of energy sourced from renewables by 2020. Biomass imports are likely to make an important contribution in the EU’s renewable energy consumption. The Southeastern U.S. is considered as one of the potential biomass import regions to the EU. The SubRegional Timber Supply Model (SRTS) was used to observe market reaction on changes in woody biomass consumption. The research area included Southeastern U.S and its coastal plain. The results from sensitivity analyses demonstrate that neither percentage of biomass delivery to EU nor moisture content of pellets significantly influence the wood market in the Southeastern United States. Next, the results from modeled scenarios show that for both regions and under all projected scenarios, price increases range from 25% up to 125%. Furthermore, the costs of EU imports are very sensitive to U.S. domestic renewable energy policy which is uncertain. Under all scenarios and for both the Southeast and coastal plain, carbon storage increased due to positive market planting response among private forest owners compare to baseline scenario. While low and medium scenarios were very similar in terms of impact on market behavior, high scenarios for both SE U.S. and coastal States’ cause the biggest impact on wood markets and natural resources in these regions.